STUDY REGARDING THE ACCURACY OF SOME METHODS USED IN THE DETECTION OF INCIPIENT OCCLUSAL CARIOUS LESIONS - Andrei Georgescu; Simona Stoleriu; Claudiu Topoliceanu; Gianina Iovan; Octavian Mihai Boaru; Sorin Andrian (Romanian Society of Oral Rehabilitation, 2015)
The aim of this study was to compare in vivo and in vitro accuracy (sensitivity and specificity) of visual inspection and laserfluorescence method in the detection of incipient occlusal carious lesions. Material and methods. 106 occlusal areas (mesial, distal, central) selected in a study group of 53 molars and bicusps forthcoming for extraction, were examined using visual inspection and laserfluorescence method using DIAGNodent device (KaVo, Biberach, Germany). After extraction, teeth were submitted to new clinical and paraclinical examen (visual inspection, laserfluorescence method). The teeth were cut in longitudinal axis and the slices were examined by optical microscopy. The results of histological examen were considered gold standard and were used to calculate the sensitivity and specificity of the tested detection methods. The statistical analysis used test Mc Nemar both for in vivo and in vitro results. Results. For carious lesions limited to external half of enamel, the in vivo sensitivity was 56% for visual inspection and 91% for laserfluorescence method. For carious lesions extended to inner half of enamel, the in vivo sensitivity was 57% for visual inspection and 90% for laserfluorescence method. For carious lesions limited to external half of enamel, the in vivo specificity was 66% for visual inspection and 86% for laserfluorescence method. For carious lesions extended to inner half of enamel, the in vivo specificity was 76% for visual inspection and 88% for laserfluorescence method. In vitro sensitivity and specificity values were lower than in vivo values, but it was not found significant statistical differences. Conclusions. The laserfluorescence examen, in vivo and in vitro, had higher sensitivity for incipient occlusal carious lesions limited to external half of enamel and higher specificity for incipient occlusal carious lesions extended in the inner half of enamel.